PENGARUH DIGITAL MARKETING DALAM UPAYA PENINGKATAN DAYA SAING DESA WISATA KUBU BAKAS KLUNGKUNG - Ketut Arjaya (Universitas Triatma Mulya, 2023)
Compared to other tourism villages, marketing through digital media in Bakas Tourism Village is still very minimal. This can be seen from several problems found by researchers related to digital marketing indicators that have not been fulfilled, including Accessibility, Interactivity, Entertainment, Credibility, Irritation and Informativenes. This study aims to analyze the influence of digital marketing including Accessibility, Interactivity, Entertainment, Credibility, Irritation and Informativenes in an effort to increase the competitiveness of Kubu Bakas Klungkung Tourism Village. The method used in this research is quantitative research method. The results of the analysis found that Accessibility, Interactivity, Entertainment, Credibility, Irritation and Informativeness partially and simultaneously have a positive and significant effect on the Competitiveness of Kubu Bakas Tourism Village. Related to the results of this study are the manager can further improve digital marketing management as an effort to increase the competitiveness of the Kubu Bakas Tourism Village.